Effectiveness of Silver Diamine Fluoride compared with Sodium Fluoride Varnish on Oral Saliva pH in the Children with Sever-Early Childhood Caries (S-ECC) - Bahareh Nazemi salman; Amirali Bakhtiary; Solmaz Taheri (Journal of Research in Applied and Basic Medical Sciences, 2022)
Background & Aims:  Colorless Silver Diamine Fluoride (SDF) solution is effective in increasing the remineralization of hard tooth tissue, and the silver ion in it has antibacterial properties. The aim of this study was to compare the effect of Sodium Fluoride (NaF) varnish with SDF on oral saliva pH in children with premature dental caries. Materials & Methods:  In this clinical trial study, 25 children with the age group of 3-6 years old were randomly selected, and then randomly divided to two groups of receiving NaF and receiving SDF. The rate of salivary pH change in both study groups was measured and recorded before treatment (baseline time), 5, 10, 20, and 30 minutes after treatment, using digital pH meter. The results were evaluated using repeated measures and independent t-test at a significance level of 0.05%. Results:  The mean salivary pH level of the SDF group in the fifth (p = 0.018), tenth (p = 0.022), and twentieth (p = 0.039) minutes after treatment was significantly higher than it in the NaF group. In the SDF group, saliva pH at 5 (p = 0.001), 10 (p <0.001), 20 (p <0.001) and 30 minutes (p = 0.002) was significantly higher than the baseline time. Conclusion:  The saliva pH of children increased significantly after using SDF compared to NaF. Due to the other positive effects of SDF in preventing caries compared to NaF, this substance is recommended for oral pH control in ECC and S-ECC treatment plans, especially in the cases where anesthesia is not possible.